Angiopoietin-like 4 stimulates STAT3-mediated iNOS expression and enhances angiogenesis to accelerate wound healing in diabetic mice - Chong, Han Chung (2015)
Impaired wound healing is a major source of morbidity in diabetic patients. Poor outcome has, in part, been related to increased inflammation, poor angiogenesis, and deficiencies in extracellular matrix components. Despite the enormous impact of these chronic wounds, effective therapies are lacking. Here, we showed that the topical application of recombinant matricellular protein angiopoietin-like 4 (ANGPTL4) accelerated wound reepithelialization in diabetic mice, in part, by improving angiogenesis. ANGPTL4 expression is markedly elevated upon normal wound injury. In contrast, ANGPTL4 expression remains low throughout the healing period in diabetic wounds. Exogenous ANGPTL4 modulated several regulatory networks involved in cell migration, angiogenesis, and inflammation, as evidenced by an altered gene expression signature. ANGPTL4 influenced the expression profile of endothelial-specific CD31 in diabetic wounds, returning its profile to that observed in wild-type wounds. We showed ANGPTL4-induced nitric oxide production through an integrin/JAK/STAT3-mediated upregulation of inducible nitric oxide synthase (iNOS) expression in wound epithelia, thus revealing a hitherto unknown mechanism by which ANGPTL4 regulated angiogenesis via keratinocyte-to-endothelial-cell communication. These data show that the replacement of ANGPTL4 may be an effective adjunctive or new therapeutic avenue for treating poor healing wounds. The present finding also confirms that therapeutic angiogenesis remains an attractive treatment modality for diabetic wound healing.